Differentiating Multisystem Inflammatory Syndrome in Children from Kawasaki Disease During the Pandemic - Seher Şener; Ezgi Deniz Batu; Ümmüşen Kaya Akca; Erdal Atalay; Müşerref Kasap Cüceoğlu; Zeynep Balık; Özge Başaran; Tevfik Karagöz; Yasemin Özsürekçi; Yelda Bilginer; Seza Özen (AVES Yayincilik, 2024)
Objective: We aimed to delineate the distinctive characteristics that aid in distinguishing between Kawasaki disease (KD) and multisystem inflammatory syndrome in children (MIS-C) with KD-like manifestations during the pandemic. Materials and Methods: We evaluated KD patients and MIS-C patients with KD-like symptoms admitted during the pandemic (between January 2021 and December 2022). Results: Thirty-three MIS-C patients and 15 KD patients were included. Kawasaki disease patients were younger than MIS-C patients (3.4 vs. 7.6 years). Rash (P = .044, 100% vs. 75.7%), oral mucosal changes (P = .044, 100% vs. 75.7%), and cervical lymphadenopathy (P = .001, 93.3% vs. 42.4%) were more common in KD. Multisystem inflammatory syndrome in children: patients had more hypotension (P = .002, 45.4% vs. 0), gastrointestinal (P < .001, 72.7% vs. 13.3%), and respiratory symptoms (P = .044, 24.2% vs. 0). Multisystem inflammatory syndrome in children patients also had low lymphocyte and thrombocyte counts and elevated levels of d-dimer, ferritin, and cardiac parameters, unlike KD patients. Multisystem inflammatory syndrome in children patients exhibited a notable reduction in left ventricular systolic function in echocardiography. Another significant difference with regard to management was the anakinra treatment, which was prescribed for MIS-C patients. Conclusion: Although MIS-C patients might display a clinical resemblance to KD, several features could help differentiate between MIS-C and classical KD. Specific clinical (hypotension, gastrointestinal, and respiratory symptoms) and laboratory (low lymphocyte and thrombocyte counts with higher C-reactive protein, ferritin, d-dimer, and cardiac parameters) features are characteristic of MIS-C. In addition, divergence in management strategies is evident between the 2 diseases, as biologic drugs were more prevalently employed in MIS-C patients than in classical KD patients.